Investigation of the relationship between DNA methylation of PTH, ESRRA, FSHR and obesity: A single center study (Bangladesh Journal of Medical Science, 2023)
Background: Obesity is a multifactorial disorder that is an important predisposing factor for a number of disorders. Genetic and epigenetic variations play important roles during the development of obesity.Method: DNA methylation is the most studied as one of the epigenetic modifications and is directly related to gene expression. Here, the methylation status of FSHR, PTH and ESRRA genes were investigated in obese patients to discover novel associations between DNA methylation and obesity phenotype. A total of 69 patients with obesity and 76 patients without obesity were enrolled in this study. DNA methylation in FSHR, PTH and ESRRA genes was analyzed.Result: There is a statistically significant association between the methylation status of ESRRA and fasting glucose (P=0.04) and BMI and methylation of the PTH gene (P=0.036) in obese subjects. In non-obese subjects, a statistically significant association was detected between adiponectin, resistin levels and FSHR methylation status. It is concluded that the methylation status of FSHR, PTH and ESRRA genes play an important role in obesity phenotype, adiponectin and resistin levels. These genes had previously been associated with obesity-related variables, but their methylation status was not highlighted.Conclusion: Our study will shed light on resolving the epigenetic contributions toward the development of obesity. Studies in the field of epigenetics will help discover predisposition markers for obesity. Based on the literature this was the first study that shows the interactions between FSHR, PTH and ESRRA methylation and obesity.Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 623-631